Impact of Hybrid Work Model on Job Satisfaction of Techies during the COVID-19 Pandemic - Gangisetty, N.; Dias, Rui; Irfan, Mohammad; Mohana, S.; M, Sandeep Kumar; Santosh, Kathari; Galvão, Rosa; Varela, Miguel (Journal of Ecohumanism, 2024)
The rise of hybrid work models, blending remote and onsite work arrangements, has become increasingly prevalent in today's workforce, especially in the IT industry. The research aims to determine the effects of a hybrid-work model on the job satisfaction of tech professionals, focusing on key factors including onsite work, remote work, flexibility, communication, and safety. Using reliability test, CFA and structural analysis, data collected from a sample of tech professionals was analysed to measure the connection among various work arrangements and satisfaction of job. The findings reveal significant positive associations between job satisfaction for both onsite and remote work. Additionally, flexibility and effective communication emerged as important factors positively influencing job satisfaction among tech workers in hybrid work environments. Furthermore, our study underscores the importance of safety considerations in hybrid work settings. While safety showed a smaller effect size than other factors, it still exhibited a significant relationship with job satisfaction, highlighting the significance of providing a safe and secure work environment for tech professionals. These findings contribute to considering how hybrid work models impact job satisfaction in the technology sector. Employers and organisations can leverage these insights to optimise their hybrid work policies, emphasising flexibility, communication, and safety factors to enhance overall job satisfaction among tech employees.